Tools for survival : what you need to survive when you're on your own - Rawles, James Wesley (Plume, 2015)
"Rawles details the tools needed to survive anything from a short-term disruption to a long-term, grid-down scenario. Field-tested and comprehensive, Tools for Survival is certain to become a must-have reference for the burgeoning survivalist/prepper movement"--